Different effects of earthworms and ants on soil properties of paddy fields in North-East Thailand - Jouquet, Pascal; Hartmann, C.; Choosai, C.; Hanboonsong, Y.; Brunet, D.; Montoroi, J.P. (Springer, 2008)
As soil engineers, earthworms and ants play major roles in soil functioning, especially in modifying soil physical and chemical properties. This study was conducted in a very constraining environment, i.e., paddy fields which have anoxic conditions (approximately four months per year), and which are affected by soil salinisation during the dry period (approximately eight months per year). This study points out that despite those very adverse conditions, soil invertebrates must be taken into account in the dynamic of soil organic and mineral properties in paddy fields. The effects of one earthworm species, Glyphodrillus sp., and an ant species, Epelysidris sp., on soil physical and chemical properties were determined through elemental soil physical and chemical properties (texture, pH, conductivity, C and N contents) and near infrared reflectance spectroscopy (NIRS) in order to evaluate their ability to influence soil organic matter quality. PCA processed with NIRS data clearly showed that biogenic structures (ant sheetings and earthworm casts) were separated from the control surrounding soil. Earthworms and ants affected differently soil properties. Glyphodrillus sp. increased the SOM content and decreased the pH on the surface of the soil. These effects were attributed to an increase in fine particle content (clay). Conversely, Epelysidris sp. only increased the content of coarse particles (sand) and did not influence either soil pH or SOM content. Soil conductivity was found to be very variable but was not significantly affected by soil invertebrates. These results show the potential of soil macro-fauna to create heterogeneity at small spatial scale and to modify the quality of surface soils even under adverse conditions like saline paddy fields.